Membangun desa cerdas: Peran digitalisasi dalam branding desa - Hidayat, Andi Ircham; Yassen, Syahruddin; Dwinanda, Giri; Nursanti, Anita (Lembaga Penerbitan, Penelitian, dan Pengabdian Masyarakat (LP3M) UNZAHLP3M, 2025)
Limited exposure to village potential, especially tourist destinations, MSME products, and public service information, leads to a low reach of official information and consistency of village image. These studies aim to build credible and easy-to-manage digital channels through the development of village websites to strengthen branding and improve services. The Participatory Action Research (PAR) approach is applied in four stages of action planning, implementation, observation, and reflection and evaluation with the active involvement of the village government and local actors. The results of the activities include the release of a responsive website that contains village profiles, activity galleries, the latest news, MSME directories, tourist information with maps, and an online letter submission feature to speed up administrative services. Apparatus capacity building is carried out through training in content management, basic SEO, media management, security & backup, traffic analytics, and SOP compliance; Evaluation was carried out by black-box functional tests, as well as performance measurements. It is concluded that this intervention can strengthen village branding, improve the consistency of publication and information coverage, and encourage local economic exposure, as well as replication as the foundation for the integration of the next